Formation of litter crusts and its multifunctional ecological effects in a desert ecosystem. Issue 4 (24th April 2018) - Jia, Chao; Liu, Yu; He, Honghua; Miao, Hai‐tao; Huang, Ze; Zheng, Jiyong; Han, Fengpeng; Wu, Gao‐Lin
Abstract: Desertification is one of the major issues in global environmental change, and it is of great concern to scientists and policy‐makers in the world. Litter crusts can be of great importance for the restoration and management of desert ecosystems. The formation of litter crusts and its ecological effects on desert surface microhabitats were studied in a wind–water erosion crisscross desert region. It was found that litter crusts, especially the four‐year litter crusts, exhibited a better soil storage capacity and temperature regulating ability when compared to the bare land, biocrusts, and two‐year litter crusts; the four‐year litter crusts significantly increased soil total porosity, soil water storage, and soil organic carbon content, but reduced soil bulk density. Furthermore, species richness, coverage, and plant height of seedlings in litter crusts were significantly greater than those in bare land and biocrusts. Although the bare land had the greatest total number of seedlings, the survival rate of seedlings was lowest there. Our findings revealed that litter crusts had significantly positive effects on soil moisture, soil temperature, soil physicochemical properties, and seedling establishment. The multifunctional ecological effects of litter crusts are more positive than lichen‐ and moss‐dominated biocrusts in desert ecosystems.